Health and nutrition - Moore-Ott, Jennifer; Youngdani, Kate; Schlessinger Media (Firm); Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2006)
This Program describes essential nutrients, including carbohydrates, fats, proteins, vitamins, minerals and water. Stresses the concept of a balanced diet, along with a full presentation of the Food Guide Pyramid and a segment on the importance of exercise for maintaining good health
Executive producer, Andrew Schlessinger, Tracy Mitchell ; graphics, Mose Aimone
Narrator: Bob Gatchel, Jeanie Stith, Scott Grimaldi, Hollis Payer
DVD format
Keywords: Nutrition; Health; Human body